Toward a synthesis of models of regulatory policy design with limited information. - Armstrong, M; Sappington, D (Springer, 2004)
We develop a simple, yet general, model that admits as special cases several key analyses of the design of regulatory policy in the presence of asymmetric information. In doing so, we help to identify the central differences and similarities among the diverse analyses in the literature.